“We Speak the Same Language, but They Don't Understand Us.” Use and Abuse of Culturalism in Medical Care for Central American Migrants in Transit Through Mexico - Stoesslé, Philippe (Frontiers in Public Health, 2022)
This article deals with cultural stereotypes towards Central American migrants in the Mexican health care system, which lead to the naturalization of the supposed cultural characteristics of these new users. Based on 21 interviews of health and administrative staff in the state of Nuevo Leon (northeastern Mexico), it shows the first recourse to culturalist explanations to describe any phenomenon related to migrants' health. According to this perspective, the health of migrants, their relation to illness, and their patterns of seeking health care would be mainly determined by characteristic cultural traits, which justify their penurious attendance at health centers, and their low adherence to treatments. The culturalist explanation of migrants' health behaviors may influence the care they receive, as well as their adherence to treatment, which ultimately reinforces the health inequalities initially highlighted. This culturalist excess is partly explained by the incorrect understanding of the directives of health authorities in favor of the integration of an intercultural perspective in health care. Despite some ongoing training in this area, it does not seem sufficient to correct this situation effectively.